PENERAPAN LATIHAN BERBASIS MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN PENCAK SILAT TUNGGAL GOLOK - Mega Dapira; Boby Agustan; Didi Muhtarom (STKIP Muhammadiyah Kuningan, 2020)
The purpose of this study was to see the effect of audio-visual media-based training on improving the skills of single golok skills in PBSS Kuningan athletes. This research is an experimental method. The study population was 30 athletes of the PBSS Kuningan club. The sample was determined as many as 10 people. The sampling technique used purposive sampling, with the criteria (1) already having the basic material of pencak silat Tunggal Golok (2) having at least 75% experience in training activities at the PBSS Kuningan club. The research instrument used in this study was a test of the correctness of the movement of pencak silat in the single category of the golok with 3 series of movement moves, using the IPSI format for the single category of the golok. The data analysis technique used the t test at the 5% significance level. To fulfill the assumptions of the research results, the analysis prerequisite tests were carried out, namely the normality test, homogeneity test and hypothesis testing. The results showed that the application of audio-visual media-based training had an effect on the single-blade pencak silat skills of PBSS kuningan athletes. This is evidenced by the results of the calculation of the final exercise test, namely t count 4.468> t table 1.83311 with a significance level of 5%.